2022
DOI: 10.1111/jocn.16302
|View full text |Cite
|
Sign up to set email alerts
|

Partnering with support persons and clinicians to improve the health care experiences of patients with cirrhosis

Abstract: Aim To explore the care experiences of Aboriginal and Torres Strait Islander Australians diagnosed with cirrhosis with a focus on support needed. Background Cirrhosis disproportionately affects Indigenous Australians, and liver diseases contribute to the mortality gap between Indigenous and other Australian adults. Design A qualitative study. Methods Using yarning methods, Indigenous patients (n = 13) and support persons (n = 3) were interviewed by an Aboriginal researcher during April‐July, 2020. Thematic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
2
2
0
Order By: Relevance
“…Although this is surprising, given the poor prognosis typically associated with HCC compared to these other cancer types, psychological reactions may be blunted due to patients undergoing HCC surveillance having cirrhosis and already considering themselves as having significant comorbidity. In fact, patients with cirrhosis may have fatalism when approaching HCC risk, thereby framing HCC development as a question of “when” instead of “if.” These patients may therefore have stronger support systems and increased resilience to cope with stressors, including positive surveillance results 36,37 . This hypothesis was supported by our semistructured interviews, in which patients with true and FP results both reported coping responses by engaging in other healthy behaviors or external support systems.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although this is surprising, given the poor prognosis typically associated with HCC compared to these other cancer types, psychological reactions may be blunted due to patients undergoing HCC surveillance having cirrhosis and already considering themselves as having significant comorbidity. In fact, patients with cirrhosis may have fatalism when approaching HCC risk, thereby framing HCC development as a question of “when” instead of “if.” These patients may therefore have stronger support systems and increased resilience to cope with stressors, including positive surveillance results 36,37 . This hypothesis was supported by our semistructured interviews, in which patients with true and FP results both reported coping responses by engaging in other healthy behaviors or external support systems.…”
Section: Discussionsupporting
confidence: 62%
“…These patients may therefore have stronger support systems and increased resilience to cope with stressors, including positive surveillance results. [36,37] This hypothesis was supported by our semistructured interviews, in which patients with true and FP results both reported coping responses by engaging in other healthy behaviors or external support systems. Providers' framing of test results, including any risk of FPs, as well as treatment options for those with newly diagnosed HCC may have also helped mitigate psychological distress, although we were unable to assess patient-provider communication as part of our study.…”
Section: Discussionsupporting
confidence: 56%
“…However, some patients with greater resistance in the management of their own symptoms also had higher external support needs. As such, healthcare providers need to evaluate the patient own coping ability and offer appropriate supports to patients in need [ 17 , 35 ] to improve the management level of symptom clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Watson et al [13] conducted a qualitative study to examine how adolescents experience anhedonia, a core symptom of depression, through semi-structural interviews of 2 patient groups: adolescents with a primary diagnosis of depression and those with elevated depressive symptoms. To date, however, only a small number of qualitative studies have been conducted for symptom analysis and clustering among patients with cirrhosis, [14][15][16][17][18] and such a qualitative study has not been reported for patients with decompensated cirrhosis.…”
Section: Introductionmentioning
confidence: 99%